2016
DOI: 10.1097/pcc.0000000000000656
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Infusion Vancomycin Through the Addition of Vancomycin to the Continuous Renal Replacement Therapy Solution in the PICU

Abstract: The addition of vancomycin to the continuous renal replacement therapy solution(s) is an effective modality that is used for delivering vancomycin continuous infusion and for ensuring therapeutic vancomycin serum plateau levels in the setting of pediatric continuous renal replacement therapy. Further studies are required to evaluate whether this delivery method can lead to improved patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
1
14
0
1
Order By: Relevance
“…These findings are also consistent with data for other drugs that are renally cleared, such as gentamicin, where increased doses are required in the intensive care setting secondary to an illness‐induced hyperdynamic state and consequent increased volume of distribution . Continuous infusions of vancomycin have been proposed as a solution to the poor attainment of therapeutic vancomycin concentrations with intermittent dosing . Overall, our data suggest that a more aggressive approach to vancomycin dosing in critically ill children and neonates is necessary.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings are also consistent with data for other drugs that are renally cleared, such as gentamicin, where increased doses are required in the intensive care setting secondary to an illness‐induced hyperdynamic state and consequent increased volume of distribution . Continuous infusions of vancomycin have been proposed as a solution to the poor attainment of therapeutic vancomycin concentrations with intermittent dosing . Overall, our data suggest that a more aggressive approach to vancomycin dosing in critically ill children and neonates is necessary.…”
Section: Discussionsupporting
confidence: 87%
“…36 Continuous infusions of vancomycin have been proposed as a solution to the poor attainment of therapeutic vancomycin concentrations with intermittent dosing. [37][38][39][40] Overall, our data suggest that a more aggressive approach to vancomycin dosing in critically ill children and neonates is necessary. Doses at the higher end of daily recommendations were required in older children, with 75% of children attaining therapeutic concentrations with doses >50 mg/kg/day.…”
Section: Discussionmentioning
confidence: 80%
“…15,34,39 Use of a loading dose prior to CIV initiation can also improve the time to target serum concentration achievement. [16][17][18][19][20][21][22][23]27,[29][30][31][33][34][35][36] Pawlotsky et al 27 showed that administration of a 7-mg/kg loading dose in neonates achieved a postloading dose serum concentration of 15 ± 8.1 mg/L, which was within their target range of 10 to 30 mg/L. Zhao et al 30 used a patient-tailored optimized dosing regimen that included a loading dose, achieving desired serum concentrations within 6 to 12 hours after starting CIV treatment in over 70% of neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Critically Ill Children. Cies et al 35 retrospectively evaluated the achievement of target serum concentrations when CIV was administered by adding vancomycin to continuous renal replacement therapy (CRRT) solutions in 11 critically ill children with acute kidney injury in a pediatric intensive care unit (PICU) in Philadelphia (Table 2). Following a loading dose, vancomycin was added directly to CRRT solution, dialysate, and/or replacement fluid with final vancomycin concentrations ranging from 18 to 30 mg/L.…”
Section: Clinical Evidencementioning
confidence: 99%
“…Pharmacokinetics and pharmacodynamics are essential factors when treating any infection and are known to undergo changes for patients in the PICU and with CRRT. [7][8][9][10][11][12][13][14][15][16][17][18][19] Therefore, the purpose of this case report is to describe the pharmacokinetics of continuous infusion doripenem in a pediatric patient receiving CRRT. The Drexel University College of Medicine Institutional Review Board approved this case report.…”
Section: Introductionmentioning
confidence: 99%